Octanoylated Ghrelin Inhibits the Activation of the Palmitic Acid-Induced TLR4/NF-κB Signaling Pathway in THP-1 Macrophages. (26th November 2012) - Liu, S. P.; Li, X. Y.; Li, Z.; He, L. N.; Xiao, Y.; Yan, K.; Zhou, Z. G.
Abstract : To investigate the effect of acylated ghrelin on the activation of TLR4/NF- κ B signaling pathway induced by palmitic acid in human monocyte-derived (THP-1) macrophages, THP-1 macrophages were cultured for 12 h by palmitic acid with various concentrations. The THP-1 macrophages was pretreated by acylated ghrelin at different doses for 4 h before cultivated by palmitic acid (200 μ mol/L) for 12 h. We observed the level of TLR4, NF- κ B p65 phosphorylation in THP-1 macrophages and TNF- α, IL-1 β in culture supernatant. TLR4 mRNA was measured by real-time PCR. TLR4 protein and NF- κ B p65 phosphorylation was measured by western blotting. The expression of TNF- α and IL-1 β was detected by ELISA. Compared to the THP-1 macrophages without palmitic acid, the level of TLR4 mRNA protein and NF- κ B p65 phosphorylation and the expression of TNF- α and IL-1 β increased after treatment by palmitic acid in a dose-dependent fashion (P < 0.05 ). Compared to the THP-1 macrophages with palmitic acid (200 μ mol/L), the level of the pervious substances decreased after preadministration by acylated ghrelin in a dose-dependent fashion. So, we make a conclusion that acylated ghrelin can regulate the activation of TLR4/NF- κ B signaling pathway and inhibit the release of inflammatory cytokines in THP-1 macrophages which are stimulated by palmitic acid in a dose-dependent fashion.